The Little Red Rescue Box - Random House (Firm) (New York, New York : Random House, 2016)
An accident-prone baby bird befriends Marshall. But when it's time for him to rejoin his flock, will he go?
On board pages.
Cover title.
Part of Little Red rescue box set ISBN 9780399551352.
New Kids Book 2023 Spring.
Keywords: Puppies -- Juvenile fiction; Birds -- Juvenile fiction; Friendship -- Juvenile fiction; Board books; Fiction